Elastic Electroadhesion with Rapid Release by Integrated Resonant Vibration. Issue 1 (26th October 2018) - Gao, Xing; Cao, Chongjing; Guo, Jianglong; Conn, Andrew
Abstract: Soft robotic grippers have gained a growing interest due to their inherent compliance which passively adapts to a variety of object shapes and electroadhesion (EA) has attracted particular attention due to its versatile, low impact adhesion. EA shows potential for the precise manipulation of thin and flexible substrates such as plastic films, which is crucial to the advancement of flexible electronics fabrication. However, the rapid release of substrates is a challenge with EA due to the residual charge and relatively slow dielectric natural relaxation time that exists when the applied voltage switched off. Here, a novel soft gripping technology that integrates a dielectric elastomer actuator with an EA into a soft, monolithic structure to achieve rapid de‐adhesion is presented. This inherently compliant device exploits resonant excitation to minimize the release period to a range of 100–500 ms, which is an improvement of at least two orders of magnitude compared with conventional EA release. The developed end effector demonstrates rapid and robust adhesion/de‐adhesion performance in a lightweight and compact form, with simplified control and low energy consumption and hence has wide application to a variety of robotic manipulation tasks. Abstract : An elastic electroadhesion (EA) membrane is developed as a soft, monolithic structure with an integrated dielectric elastomer actuator (DEA). Applying a voltage to the EA electrodes generates an electroadhesive force that can pick up objects. Resonant excitation of the DEA electrode achieves rapid de‐adhesion in under 500 ms, which is two orders of magnitude faster than conventional EA pads.